(untitled) (Theatrum historiae, 2018)
A junkwoman/Lumpensammlerin ‒ a collector of waste rags, glass and bones appeared in the society in a broader context. Someone perceived her as a peculiar character of that time; others considered her to be the poorest being, and for the others she was a necessary labour force recycling solid municipal waste. Financial authorities were interested in her because she collected rags that were in a special customs regime and under official supervision. Permission to such work was issued by the district council, but a junkwoman ranked neither among tradeswomen nor doortodoor sellers. She became a subject matter for artists, journalists and cabaret performers.